Estrategia de capacitación y evaluación de resultados del personal directivo en la municipalidad distrital de Curgos, provincia de Sánchez Carrión, año 2015 - Marquina Altamirano, Miriam Vanessa (2016)
This research was conducted in the District Municipality of Curgos, in the mountains of the region La Libertad, Peru; Its main objective is to explain that m way the Training Strategy influences the Evaluation of results. Examined problematic reality has and has formulated the research question: How does the training strategy influences the Evaluation of results management in the District Municipality of Curgos, Sánchez Carrión Province, 2015?. For Data Collection itself to have looked at two populations, constituting themselves Samples: Ten managers responsible for the area and the municipal manager UN. They were the Revised reports Institution About Mayoral Resolutions authorizing Licensing Training Attend one Outside the town, themes, locations, times and other required. They have the APLICADO Surveys and interviews, obtaining the results that have been the basis for the analysis and corresponding discussion, getting to demonstrate the validity of the hypothesis: "The Training Strategy, including diagnosis, programming and implementation directly influences the evaluation of results management in the District Municipality of Curgos, Sánchez Carrión Province, Year 2015". Finally they formulated the conclusions and recommendations: the main conclusion states that training needs are varied and specialty, so managers travel outside the city to participate in programs organized by public and private entities; therefore topics, calendar, schedules, city, institutions and speakers are not under the control of the municipal entity. It is recommended that the authorities and managers responsible should be informed in advance about the availability of courses and other events nationwide, which meet the needs of the charges, and schedule equitable participation of staff, who at the end should disseminate the new knowledge learned among his coworkers.